Modern Wound Care Application: A Literature Review - Khaerotib; Yuly Peristiowati; Ratna Wardani (International Journal of Science and Society, 2021)
Wounds are damage to tissue structures and normal anatomical functions as a result of pathological processes originating from internal and external that hit certain organs. Wounds can be classified based on anatomical structure, properties, the healing process, and length of healing. The literature review aims to find out the modern application of the wound care-related wound healing process. Literature review through several stages, namely making questions, identification, eligibility, selection of article inclusion, and screening. The Selection Process is listed in the framework of the review literature and obtained the results of article 7 articles. The data showed different results adjusted to the system and the conditions of where the research was conducted. The results of the reviewed article focus on explaining the patient's comfort level and more significant healing process. Modern wound care application has been proven to provide comfort to patients in carrying out the wound healing process, and is very helpful for nurses in providing nursing services. The application of modern wound care is a wound care technique that will develop at any time based on the development of nursing science, in which case it focuses on the level of comfort of patients in receiving health services related to wound care. So nurses urgently need to improve and develop science related to the application of modern wound care that will support patient comfort in wound care and accelerate the wound healing process well.